What matters to SRI investors? - Peer Osthoff (University of Cologne, Centre for Financial Research (CFR), 2008)
In this paper I investigate the investment behavior of SRI investors based on SRI mutual fund flows. Specifically, I analyze how SRI investors react to past performance and ethical standards. This empirical study shows that over the years along with the development of the SRI fund market, the performance sensitivity of SRI investors has increased. Today, SRI investors chase past top performing funds at least as much as conventional investors do. Besides performance, SRI investors care about the actual ethical standards of SRI funds. SRI funds with high ethical standards regarding the positive rating and especially regarding environment attract higher inflows. I also find that SRI investors are more likely to reinvest in the same fund. Overall, I conclude that, like conventional investors, nowadays SRI investors chase previously top performing funds, but additionally pay attention to the actual ethical standards of their investments.
Keywords: G11; G20; M14; 330; Socially Responsible Mutual Funds; Socially Responsible Investing; Ethical Investment; Kapitalanlage; Ethische Geldanlage; Anlageverhalten; Investmentfonds; USA